A Review of Consequences of Poverty on Economic Decision-Making: A Hypothesized Model of a Cognitive Mechanism - Adamkovič, Matúš; Martončik, Marcel (Frontiers in Psychology, 2017)
This review focuses on the issue of poverty affecting economic decision-making. By critically evaluating existing studies, the authors propose a structural model detailing the cognitive mechanism involved in how poverty negatively impacts economic decision-making, and explores evidence supporting the basis for the formation of this model. The suggested mechanism consists of a relationship between poverty and four other factors: (1) cognitive load (e.g. experiencing negative affect and stress); (2) executive functions (e.g. attention, working memory, and self-control); (3) intuition/deliberation in decision-making; and (4) economic decision-making (e.g. time-discounting and risk preference), with a final addition of financial literacy as a covariate. This paper focuses on shortfalls in published research, and delves further into the proposed model.